Determination of the Reaction During the Interaction of Cotton Flyers with the Multifaceted Network Surface of the Small Lot Cleaner - Murodov Orif Jumayevich; Pardayev Bahrom Choriyevich; Qulqorayev Abdumumin Xolmurot ugli (Genius Journals, 2022)
In the article, the new constructions of the piled drum and the polygon mesh surface for cleaning cotton from the initial small debris are presented, and the dynamics of interrelationships between the cotton fabric and the polygon surface are theoretically and practically studied.
Keywords: Cotton; integriruya; cotton dynamics; tensile strength